The Revolution in Crisis: A History of Human Rights in Mexico, 1970-1980 - Quezada, Ariana (My University, 2016)
This work looks at the proliferation of human rights in Mexico in the 1970s. By looking at how the term entered Mexico, one can determine that individualistic notions of rights (human rights) proliferated in Mexico in the late 1970s as a result of the arrival of South American refugees, the rise of a freer press, through Mexico's first NGO (CENCOS), and the 1979 Jimmy Carter visit to negotiate an oil deal. The diffusion of internationalist notion of rights reveals a shift from a corporate protection of rights to more individualist conceptions of rights--particularly as Mexico made a shift to Neoliberal economic politics. The consequences of human rights development in Mexico have had numerous consequences, one being that Mexico avoided international scrutiny for its human rights violations until the 1990s. It avoided such scrutiny precisely because of its relationship with the United States and also because it appropriated the language of rights protections by welcoming South American political refugees fleeing military dictatorships. As such, this work reveals the unique trajectory of the rise and usage of international human rights.
Keywords: human rights; México 1970s; Luís Echeverría; John P. Humphrey; Jimmy Carter; José López Portillo; Julio Scherer García; International Women's Year Conference (IWY); Charter of Economic Rights and Duties of States; Proceso Magazine; U.S.-Mexico Relations 1979; López Portillo-Carter